2005
DOI: 10.1038/sj.npp.1300773
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Persistent Sensitization to the Reinforcing Effects of Cocaine

Abstract: The development of drug addiction involves a transition from recreational use to compulsive drug seeking and taking, and this progression can occur rapidly with cocaine use. These data highlight the importance of early drug exposure and the development of drug dependence; however, little experimental attention has been paid to this phenomenon in animal models of drug abuse. The present experiments demonstrate a progressive and rapid sensitization to the reinforcing strength of cocaine assessed using a progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
67
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 55 publications
11
67
2
Order By: Relevance
“…A 1-day abstinence period was used to provide consistency with our previous reports (Mateo et al, 2005;McCracken et al, 2005;Morgan et al, 2006). No differences in daily intake (Figure 3a) or total intake were observed between groups (Figure 3b).…”
Section: Behavioral Datamentioning
confidence: 67%
“…A 1-day abstinence period was used to provide consistency with our previous reports (Mateo et al, 2005;McCracken et al, 2005;Morgan et al, 2006). No differences in daily intake (Figure 3a) or total intake were observed between groups (Figure 3b).…”
Section: Behavioral Datamentioning
confidence: 67%
“…Morgan et al [14] showed that final ratios generally increase as long as the quantity animals are permitted to self-administer during training is restricted. Figure 5 shows the expected escalation of final ratios with only a single day of training (filled circles).…”
Section: Sequence Of Pharmacological Events and Abstinencementioning
confidence: 99%
“…Morgan and colleagues [14] showed that final ratios were more likely to increase at higher unit doses, with 1.5 mg/kg/inj being optimal. Note that the 1.5 mg/kg/inj cocaine dose occurs at the top of the PR dose effect curve, as illustrated in figure 2, [15,16,14] and is selected over lower doses (0.75 mg/kg/inj) in choice experiments [15]. Thus the dose which is most likely to push the addiction process forward is also the most reinforcing dose and the one animals are most drawn toward if given a choice.…”
Section: Progressive Ratio Training and Final Ratio Escalationmentioning
confidence: 99%
See 2 more Smart Citations